Similarities between Reproductive and Immune Pistil Transcriptomes of Arabidopsis Species - Mondragón-Palomino, Mariana (Plant Physiol, 2017)
Independent lines of evidence suggest that members from ancient and polymorphic gene families such as defensins and receptor-like kinases mediate intercellular communication during both the immune response and reproduction. Here, we report a large-scale analysis to investigate the extent of overlap between these processes by comparing differentially expressed genes (DEGs) in the pistil transcriptomes of Arabidopsis thaliana and Arabidopsis halleri during self-pollination and interspecific pollination and during infection with Fusarium graminearum. In both Arabidopsis species, the largest number of DEGs was identified in infected pistils, where genes encoding regulators of cell division and development were most frequently down-regulated. Comparison of DEGs between infection and various pollination conditions showed that up to 79% of down-regulated genes are shared between conditions and include especially defensin-like genes. Interspecific pollination of A. thaliana significantly up-regulated thionins and defensins. The significant overrepresentation of similar groups of DEGs in the transcriptomes of reproductive and immune responses of the pistil makes it a prime system in which to study the consequences of plant-pathogen interactions on fertility and the evolution of intercellular communication in pollination.